DETERMINANTS OF DISASTER MITIGATION FACILITIES IN INDONESIAN REGENCIES/CITIES: AN ANALYSIS BASED ON PODES 2024 - Ar Rifqiy, Izzuddin (Indonesian Journal of Environment and Disaster, 2026)
Indonesia is widely recognized as one of the most disaster-prone nations globally; however, mitigation capacities at the regional level remain uneven. This study aims to analyze the determinants influencing the availability of disaster mitigation facilities across 514 regencies/cities in Indonesia. Utilizing secondary data from the 2024 Village Potential Statistics (PODES), the Indonesian Disaster Risk Index (IRBI), and other socio-economic indicators, this research employs multiple linear regression models to examine four mitigation indicators: Early Warning Systems (EWS), water area maintenance, safety equipment, and evacuation signage. The results reveal a critical gap between risk and readiness; regions with high disaster risk indices tend to have fewer structural mitigation facilities, suggesting significant resource constraints. On a positive note, social capital (gotong royong) and the Human Development Index (HDI) consistently prove to be significant drivers enhancing preparedness across all models. Conversely, poor telecommunication infrastructure serves as a major barrier to effective EWS and mitigation coordination. This research recommends strengthening community-based policies, improving digital infrastructure equity, and providing specific fiscal interventions for high-risk areas with low economic capacity.